Pulai Leaves (Alstonia scholaris) as a Source of Bioactive Compounds: Phytochemistry, Bioactivities, and Application Prospects - Dikianur Alvianto; Nuzlul Musdalifah; Nova Solina Purba; Lisa Fitri Rahayu; Adhian Dini Khoirina; Taufikkilah Romadhon (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Alstonia scholaris (L.) R.Br. leaves represent a promising natural resource for the development of food and non-food products owing to their diverse bioactive constituents. This review aimed to synthesize current knowledge on the morphology, phytochemical profile, biological activities, and development prospects of A. scholaris leaves. A narrative literature review was conducted using publications retrieved from Google Scholar, PubMed, ScienceDirect, SpringerLink, and Scopus, focusing on studies published between 2015 and 2025. The reviewed literature indicates that the leaves are rich in monoterpenoid indole alkaloids, phenolic compounds, flavonoids, terpenoids, saponins, and steroids. Experimental studies have demonstrated antioxidant, antimicrobial, anti-inflammatory, antihyperglycemic, hepatoprotective, antifungal, and renoprotective activities against diabetic nephropathy. Direct applications have primarily been limited to herbal tea, antioxidant gel formulations, and the exploration of bioactive compounds as pharmaceutical candidates, whereas their utilization as functional foods, nutraceuticals, herbal cosmetics, and natural preservatives remains largely prospective. Future research should emphasize raw material standardization, extraction optimization, toxicological evaluation, and preclinical and clinical validation to facilitate the development of safe, effective, standardized, and sustainable products. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-beingSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production